Online-Based Arabic Learning Management During the Covid-19 Pandemic Era: Plan, Implementation and Evaluation - Muhyidin Yahya; Maftuhati Maftuhati; Abdul Hayyi Mustofa; Zakiyah Arifa (Universitas Islam Negeri Palangka Raya, 2021)
Currently, Arabic language learning is required to be held online. In this situation, the government has forced to announce instructions for implementing online learning since March 2020. However, these instructions have made Arabic teachers experiencing difficulties in implementing online learning. Innovative learning management is highly needed to overcome these problems. Therefore, this study aims to provide an overview of the management of Arabic language learning, especially in planning, implementing, and evaluating, organized by teachers who are members of the Arabic teachers